1992
DOI: 10.1002/j.1460-2075.1992.tb05200.x
|View full text |Cite
|
Sign up to set email alerts
|

Human p68 kinase exhibits growth suppression in yeast and homology to the translational regulator GCN2.

Abstract: The human p68 kinase is an interferon‐regulated enzyme that inhibits protein synthesis when activated by double‐stranded RNA. We show here that when expressed in Saccharomyces cerevisiae, the p68 kinase produced a growth suppressing phenotype resulting from an inhibition of polypeptide chain initiation consistent with functional protein kinase activity. This slow growth phenotype was reverted in yeast by two different mechanisms: expression of the p68 kinase N‐terminus, shown to bind double‐stranded RNA in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
255
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(271 citation statements)
references
References 57 publications
(39 reference statements)
14
255
0
Order By: Relevance
“…dsRNA-dependent protein kinase is normally activated in response to viral attack, and the depression of protein synthesis resulting from phosphorylation of eIF2a constitutes one of the major ways in which viral replication is impaired (Clemens, 1997). However, PKR can also exert effects in uninfected cells and can be a potent growth inhibitory protein when activated (Chong et al, 1992). dsRNA-dependent protein kinase is also linked to the induction of pro-apoptotic genes by dsRNA, and may trigger cell death in response to viral infection and possible tumorigenesis (Balachandran et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…dsRNA-dependent protein kinase is normally activated in response to viral attack, and the depression of protein synthesis resulting from phosphorylation of eIF2a constitutes one of the major ways in which viral replication is impaired (Clemens, 1997). However, PKR can also exert effects in uninfected cells and can be a potent growth inhibitory protein when activated (Chong et al, 1992). dsRNA-dependent protein kinase is also linked to the induction of pro-apoptotic genes by dsRNA, and may trigger cell death in response to viral infection and possible tumorigenesis (Balachandran et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of the PKR mutants PKR ⌬362-367 in pCDNA1neo (Invitrogen) and of PKR K296R, PKR 1-296, and PKR 244-551 in pET11a (Novagen) and pCDNA1neo was previously described (4,17,41,43). For construction of GAL4 transcriptional activation domain (AD) and GAL4 DNA-binding domain (BD) fusions, the NdeI linker sequence, ccatatgg, was ligated into the SmaI site of pGAD424 (AD) and pGBT9 (BD; Clontech) to generate pGAD425 and pGBT10, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas yeast cells lacking GCN2 are unable to grow on medium containing 3-AT, low level expression of heterologous PKR or PERK kinases confers a 3-AT-resistant phenotype (8,9). In addition, high level expression of PKR or PERK inhibits yeast cell growth by impairing general translation (8,10,11). Biochemical analyses demonstrated that PKR and PERK phosphorylate yeast eIF2␣ on Ser 51 both in vivo and in vitro (8,11).…”
mentioning
confidence: 99%